Between double absence and transnational professional – the unrevealed side of scientific mobility - Izabela Wagner (Comunicação e Sociedade, 2015)
The paper concerns the situation of the majority of mobile scientists working in the international prestigious research laboratories in 21st century. I point out the lag between official communication about open access and democratic and fair selections which occur in scientific careers all the time and unspoken issues related with ethnical and national discrimination in the workplaces. The problem of ethnical discrimination is omitted in the sociological literature issue however, the ethnographic data provided from scientific laboratories indicates that the ethnicity and origin (as well as the nationality of scientist) play an important role. I employ in this paper the Abdelmalek Sayad’s concept of “double absence”, showing that the situation of “foreigner” scientists (majority of the PhD students and post-docs working abroad) is similar to other categories of migrants.